2009
DOI: 10.1103/physrevc.79.044904
|View full text |Cite
|
Sign up to set email alerts
|

Energy dependence of transverse momentum fluctuations inPb+Pbcollisions at the CERN Super Proton Synchrotron (SPS) at20Atoet al.

Abstract: Results are presented on event-by-event fluctuations of transverse momenta p T in central Pb + Pb interactions at 20A, 30A, 40A, 80A, and 158A GeV. The analysis was performed for charged particles at forward center-ofmass rapidity (1.1 < y * π < 2.6). Three fluctuation measures were studied: the distribution of average transverse momentum M(p T ) in the event, the p T fluctuation measure, and two-particle transverse momentum correlations. Fluctuations of p T are small and show no significant energy dependence … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Their main focus is the search for possible structures in the QCD phase diagram with various fluctuation and correlation observables for various energies and colliding systems [210]. In particular, NA49 and NA61/SHINE obtained results on the scaled variance [211][212][213][214], strongly intensive quantities [211,[215][216][217][218][219][220], intermittency [221][222][223], and many others [224][225][226][227][228]. Also, the HADES experiment at GSI Darmstadt, which measures at very low collision energies, has some capability to address fluctuation observables.…”
Section: Introductionmentioning
confidence: 99%
“…Their main focus is the search for possible structures in the QCD phase diagram with various fluctuation and correlation observables for various energies and colliding systems [210]. In particular, NA49 and NA61/SHINE obtained results on the scaled variance [211][212][213][214], strongly intensive quantities [211,[215][216][217][218][219][220], intermittency [221][222][223], and many others [224][225][226][227][228]. Also, the HADES experiment at GSI Darmstadt, which measures at very low collision energies, has some capability to address fluctuation observables.…”
Section: Introductionmentioning
confidence: 99%
“…Such fluctuations have been proposed as experimental observable for the detection of a CEP in a heavyion collision [11,12]. However, measurements in the NA49 experiment could hardly find any non-monotonic behavior [13,14]. It has later been shown that higher moments or cumulants and their ratios are even more sensitive to a critical structure [15].…”
Section: Introductionmentioning
confidence: 99%
“…Event-by-event p T fluctuations have been studied in nucleus-nucleus (A-A) collisions at the Super Proton Synchrotron (SPS) [10][11][12][13][14] and at the Relativistic Heavy-Ion Collider (RHIC) [15][16][17][18][19][20], where dynamical fluctuations have been observed. Fluctuations of p T were found to decrease with collision centrality, as generally expected in a dilution scenario caused by superposition of partially independent e-mail: alice-publications@cern.ch particle-emitting sources.…”
Section: Introductionmentioning
confidence: 99%